Optimisation of bioprinting protocols for improved tissue formation. A fight against gravity - Nielsen-Munk, Cornelia (My University, 2023)
Tissue generation on demand gradually transforms into reality. Generated tissues can be used for repairing native damaged tissues or be used as tissue models for evaluation of drug efficiency or toxicity. The microfluidic-based bioprinter Biopixlar, enables complex tissue generation with high-precision cell positioning. Yet, this technology could benefit from further optimisation for improved tissue formation. This project aimed to enhance printability (i.e. ease of viable cell attachment on a surface) through attempts to decrease the cell sedimentation rate, caused by gravitational force, within the printhead of Biopixlar. The project intended to exchange current printing solution (i.e. the solution in which cells are hosted during the printing process), containing polyethylene glycol (PEG) in phosphate saline buffer (PBS), to a solution with the non-ionic density gradient medium Histodenz. Mesenchymal stem cells (hMSCs) were chosen as a model cell line as they are promising cells, commonly used in regenerative medicine. Biopixlar printability was evaluated by the number of printed cells, cell viability, uniformity of printed shape and duration of printing as well as length of the printed pattern. Two printing strategies was performed, the first where continuous long lines were printed and the second where pairs of lines where printed with intermediate breaks. By the exchange of printing solution to Histodenz 12 % [w/v], the printing duration time was improved by 500-600 %. Furthermore, the shape uniformity and cell count showed increased stability between measurements when using Histodenz solutions compared to the current printing solution. In addition, cell viability after exposure to Histodenz was addressed using cell viability assays (MTS/MTT) on cultured cells supplemented with live/dead staining of printed cells. The results indicate 66-83 % cell viability, which is lower than usually obtained with currently used printing solution (over 95 %). However, these results were generated in extreme conditions (printing time) and therefore require further investigation and optimisation. In conclusion, the use of Histodenz solution 12 % [w/v] improved Biopixlar printing of hMSCs and were considered superior over PEG solution, regardless of observed reduced cell viability.
Keywords: printability; mesenchymal stem cells; Histodenz; polyethylene glycol; printing solution; bioprinting